Development of Rubita Media Based on QR Code with Strengthening the Character of Hard Work of Class IV Elementary School - Lindawati Lindawati; Sri Murdiyah; Sutansi Sutansi (JED (Jurnal Etika Demokrasi), 2020)
Abstract. Indonesia is a country that is rich in culture, each region has cultural characteristics that make the diversity of the nation, one of which is the archipelago dance. However, the archipelago dance is less attractive to students and begin to be ignored and even forgotten by the younger generation, they are more familiar with modern dance than the archipelago dance. This development research aims to test the feasibility of a QR Code-based Rubita media in terms of attractiveness, validity, and practicality. The research method used is a modification of the Borg and Gall development model that includes stages (1) potential and problems, (2) data collection, (3) product design, (4) design validation, (5) design revision, (6) testing try the product, (7) product revision, (8) trial use. The results of the research and development of QR Code-based Rubita media show the level of validity of the material experts by 94%, validation of media experts by 98%, and validation from users (teachers) by 96% percentage of QR Code-based Rubita media including highly valid media. The results of product trials in the field show that the appearance of instructional media is very compatible with learning in elementary schools, with the combination of shapes and colors on the QR Code-based Rubita makes students very interested in participating in learning with these media.Keywords: Rubita based on QR Code; Cultural Diversity; Elementary SchoolAbstrak.  Indonesia adalah negara yang kaya akan budaya, setiap daerah memiliki ciri khas budaya yang menjadikan keanekaragaman bangsa, salah satunya adalah tari nusantara. Namun, tari nusantara kurang diminati oleh siswa dan mulai diabaikan bahkan dilupakan oleh generasi muda, mereka lebih mengenal tari modern daripada tari nusantara. Penelitian pengembangan ini memiliki tujuan untuk menguji kelayakan media Rubita berbasis QR Code dari segi kemenarikan, kevalidan, dan kepraktisan. Metode penelitian yang digunakan adalah modifikasi dari model pengembangan Borg and Gall yang meliputi tahap (1) potensi dan masalah, (2) pengumpulan data, (3) desain produk, (4) validasi desain, (5) revisi desain, (6) uji coba produk, (7) revisi produk, (8) uji coba pemakaian. Hasil penelitian  dan pengembangan media Rubita berbasis QR Code menunjukkan tingkat kevalidan dari ahli materi sebesar 94%, validasi ahli media sebesar 98%, dan validasi dari pengguna (guru) sebesar 96% persentase media Rubita berbasis QR Code termasuk media yang sangat valid. Hasil uji coba produk di lapangan menunjukkan bahwa tampilan media pembelajaran sangat sesuai dengan pembelajaran di Sekolah Dasar, dengan perpaduan bentuk dan warna-warni pada Rubita berbasis QR Code  membuat siswa sangat tertarik untuk mengikuti pembelajaran dengan media tersebut.Kata Kunci: Rubita Berbasis QR Code; Keberagaman Budaya; Sekolah Dasar